2015
DOI: 10.1007/s11626-015-9888-9
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory response of cultured rat synoviocytes challenged with synovial fluid from osteoarthritis patients correlates with their radiographic grading: a pilot study

Abstract: The inflammatory nature of synovial fluid (SF) of varying grade osteoarthritis (OA) patients was estimated by measuring pro-inflammatory factors and through a unique cell-challenge experiment. SF samples were collected from six OA and one non-OA patient; spanning Kellgren-Lawrence (KL) grades were analyzed for interlukin-1-beta (IL-1β), nitric oxide (NO) and its derivatives, and glycosaminoglycan (GAG). Levels of IL-1β, NO, and GAG in SF did not correlate with KL grades of the patients studied. In the cell-cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The novelty of the present data is the SF challenge test that was designed to study the dynamics of modulation in inflammatory microenvironment at joint in terms of classical inflammatory mediators and MMPs expression. These experiments were based on our previous learning that OA SF holds inflammatory milieu of various cytokines and chemokines and can be used to study the disease specific responses on cell lines [ 14 ]. Most of the etiopathology of OA spins around the synovium-SF-cartilage axis, wherein SF occupies the central position.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The novelty of the present data is the SF challenge test that was designed to study the dynamics of modulation in inflammatory microenvironment at joint in terms of classical inflammatory mediators and MMPs expression. These experiments were based on our previous learning that OA SF holds inflammatory milieu of various cytokines and chemokines and can be used to study the disease specific responses on cell lines [ 14 ]. Most of the etiopathology of OA spins around the synovium-SF-cartilage axis, wherein SF occupies the central position.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1β expression in the SF treated SW982 was tested by qPCR and the values were normalized against β-actin gene. SF challenge test was developed and standardized by our research group and was successfully used to study OA specific responses [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Lastly, the maximum differentiation of ThP1 and HSCs into the effector cells was seen after the SF treatment of KL grade III. This is likely to be the effect of the highest inflammatory milieu present in the KL grade III SF samples as reported by the authors in their previous publications [ 40 ]. On the other hand, this inflammatory milieu was found reduced in the KL grade IV SF samples as an effect of near-total worn-out cartilage in advanced OA [ 41 ] and is a possible reason for the relatively lower number of differentiated cells after the SF treatment of KL grade IV samples.…”
Section: Discussionmentioning
confidence: 81%
“…The hypothesis of the in vitro cell differentiation assay was to test the role of OA SF in the maturation of MCPs by providing the necessary cocktail of cytokines, cell degradation products, and immunoglobulins. In the previous studies, the authors showed that this cocktail can be used to induce inflammation in SW982, U937, HIG82 and ThP1 cell lines [ 1 , 40 , 41 ]. As demonstrated by these assays, the differentiation of HSCs and ThP1 cells into FCERI+ and HLA-DR+/CD206+ phenotypes, respectively, after SF treatment, indicate a decisive role of OA SF in the differentiation of polarised cells into effector cells such as mast cells and macrophages ( Figure 5 a–c).…”
Section: Discussionmentioning
confidence: 99%
“…OA SF plays a major role in maturation of MCPs by providing necessary cocktail of cytokines, cell degradation products, and immunoglobulins. In our previous studies, we showed that this cocktail can be used to induce inflammation in HIG82, SW982, ThP1 and U937 cell lines [13,39,40]. As demonstrated by in vitro cell differentiation assays, differentiation of HSCs and ThP1 cells into FCERI+ and HLA-DR+/CD206+ phenotypes, respectively after SF treatment, indicate a decisive role of OA SF in differentiation of polarised cells into effector cells such as mast cells and macrophages (Figure 4 -a, b, c).…”
Section: Discussionmentioning
confidence: 99%